PENGARUH UKURAN PARTIKEL BERAS HITAM (Oryza sativa L.) TERHADAP RENDEMEN EKSTRAK DAN KANDUNGAN TOTAL ANTOSIANIN - Maulida, Ria; Guntarti, Any (Universitas Ahmad Dahlan, 2015)
Black rice has been tested for its high anthocyanin content. Black rice can be one of the potential sources of anthocyanin. Particle size is one of factors which influences amount of isolated biocompound in maceration process. Decreasing particle size can increase the amount of isolated biocompound and extract yield value. The high value of extract yield shows effectiveness of maceration process. In this research, particle size variation has been done maceration process for investigating its influence on black rice extract yield and total anthocyanin content of maceration result. This study used black rice ( Oryza sativa L.) from Beringharjo market, Yogyakarta. Maceration with solvent of ethanol 96% add ed HCl 37% until pH 1,0(1:6) is done for 6 x 24 hours, with particle size variation: mesh 20/40, 40/60 and whole bran of black rice. Data of extract yield and total anthocyanin content are analyzed by using one-way ANOVA with confidence level 95%. The results revealed that extract yield and total anthocyanin content of black rice extract with particle size variation: mesh 20/40, 40/60 and whole bran of black rice intact 6%; 16%; 11,26%; and 30,76 mg/100 g; 1167,80 mg /100 g; 322,23 mg/100 g, respectively. There is significant difference between tested groups (P< 0,05). We concluded that particle size of black rice influences extract yield and total anthocyanin content of maceration result.